1994
DOI: 10.1111/j.1365-2362.1994.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary leukotrienes in sickle cell disease: possible role in the inflammatory process

Abstract: Sickle cell (HbSS) disease is associated with rheological and inflammatory stresses within the microcirculation. In order to determine the role of leukotrienes in the inflammatory processes in HbSS patients, we analysed plasma and urine levels of leukotrienes (LT); LTB4, LTC4, LTD4, and LTE4 as indicators of their in vivo metabolism. Plasma and urine level samples of 15 HbSS patients in steady-state and age-matched healthy, homozygous (HbAA) controls were extracted for leukotrienes and quantitated by HPLC. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…For example, net loss of GSH may arise because of increased excretion of GSH adducts as mercapto products (8) or via increased biliary excretion (6). Additionally, urinary excretion of cysteinyl-leukotrienes is reported to be increased in SCD (20). Leukotrienes are biologically potent eicosanoids that are derived from arachidionic acid and have significant roles in the modulation of the inflammatory process, cell adhesiveness, and vascular tone in SCD (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, net loss of GSH may arise because of increased excretion of GSH adducts as mercapto products (8) or via increased biliary excretion (6). Additionally, urinary excretion of cysteinyl-leukotrienes is reported to be increased in SCD (20). Leukotrienes are biologically potent eicosanoids that are derived from arachidionic acid and have significant roles in the modulation of the inflammatory process, cell adhesiveness, and vascular tone in SCD (38).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of erythrocyte GSH and measurement of its concentration were performed using a Hewlett-Packard 1100 HPLC system (Hewlett-Packard, Avondale, PA) equipped with a reverse-phase ODS Hypersil column (5 m, 4.6 ϫ 200 mm; Agilent Technologies, Wilmington, DE) and fluorescence detector (model HP 1046A; Hewlett-Packard) as previously described by us (3,20,26,28). Elution of the GSH was accomplished with a 3-13.5% acetonitrile linear gradient in 1% acetic acid (pH 4.25) at a flow rate of 1.1 ml/min.…”
Section: Sample Analysesmentioning
confidence: 99%
“…15,19 The ELISA kits were purchased from Neogen (Louisville, KY). Curve fitting of the standard and calculation of the amount of metabolite were performed with a weighted nonlinear ELISA program.…”
Section: Sample Collectionmentioning
confidence: 99%
“…[10][11][12] Some lung complications in SCD result from direct or indirect effects of pulmonary microvascular occlusion by sickled erythrocytes and their adhesion to the vascular endothelium, 13,14 leading to release of potent vasoactive molecules, including prostacyclin, thromboxane A 2 , and LTC 4 . 15,16 Indeed, the initiation, progression, and resolution of vaso-occlusive pain episodes due to red blood cell sickling and adhesion to endothelium in the affected tissues have been characterized as "reperfusion injury." 17 Homozygous hemoglobin SS (HbSS) disease patients in steady state have higher circulating thromboxane B 2 and LTC 4 than do control (HbAA) individuals, suggesting a greater expression and activity of LTC 4 synthase.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of this intermediate forms LTB 4 , a potent leukocyte chemoattractant that also displays leukocyte activating functions (17). Regarding hemolysis-related inflammatory conditions, it has been shown that increased LT concentrations are found in plasma and urine of SCD patients at steady state (18,19), and that plasma levels of LTB 4 are further increased during vasoocclusion and acute chest syndrome episodes (20).…”
mentioning
confidence: 99%